Strategies for promoting active and healthy aging in elderly people (Research, Society and Development, 2025)
The following study aims to identify the main strategies described in the literature for promoting active and healthy aging in the elderly. This is an integrative literature review conducted between February and May 2024. The initial search resulted in 358 articles, with 348 found in the LILACS database, 4 in MEDLINE, and 6 in SCIELO. After applying inclusion and exclusion criteria, 16 articles published between 2020 and 2024 were analyzed, involving various methodological approaches. The analyzed studies highlight strategies such as regular physical activity, reduction of sedentary behavior, digital inclusion, participation in social groups, cognitive stimulation, educational activities, and strengthening of self-care. These strategies demonstrated positive impacts on the physical, mental, and social dimensions of elderly health. Additionally, the nurse’s central role in promoting health through educational, welcoming, and interdisciplinary interventions was evident. However, the studies also point out challenges, such as the limitation of care to biological aspects, low adherence to public programs, and the need to expand access to technologies and preventive practices. Therefore, it is concluded that healthy aging requires effective public policies, adequate professional training, and greater integration between health, technology, and social inclusion.